Draft basic methodological principles governing the compilation of the system of statistical balances of the national economy - United Nations. Secretariat ([n.a]: United Nation, 1986)
The Basic Mathodological Principles Governing the Compilation of the systems of Statistical Balances of the National Economy replace the document entitled "Basic principles of the System of Balances of the National Economy", which was adopted by the United Nations Statistical Commission in 1971 as an official document (Series F, No. 17). The current document is issued in two volumes. Volume I describes the basic methodological principles and volume II contains the classification of the Branches of the National Economy of the countries members of CMEA and the System of Indicators of Social Statistics.
Introduction -- 1. Basic concepts and Definitions -- 2. The balance of the production consumption and accumulation of the Global Social Product ( The Material balance) -- The Balance of the production, Distribution, Redistribution -- 4. The Input-Output Table -- 5. The Manpower Balance -- 6.The indicators of the National Wealth and the Balance of Fixed Assets -- 7. The Indicators of the Incomes and Consumption of the population -- The Balance of Non-Material services
Keywords: System of Balances -- National Economy; Economic Statistics; Basic Mathodological Principles -- System of Balance -- National Economy